PENERAPAN JURNALISME DAMAI DALAM PEMBERITAAN KUDETA MYANMAR DI MEDIA ONLINE KOMPAS.COM - Ulima Sri Amelia; Dewi Sukartik (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Myanmar coup d'etat again, military groups take over state power. This is inseparable from the world's eyes, and this is where the media plays a big role in guiding the views and opinions of the public. Media Be a pioneer of peace. So the purpose of this study is to find out how the application of Peace Journalism in reporting the Myanmar coup in the online media Kompas.com.This study uses a qualitative descriptive method with a framing model from Robert Entman. The results show that Kompas.com framed the coup as a crucial issue involving the safety of many lives. In general, Kompas.com seems to have implemented Peace Journalism. However, if we look more deeply, Kompas.com still indicates that there are subjective opinions and title dictions that lead to provocation or truth orientation.